Composites for marine and offshore applications : novel bismaleimide/diallyl bisphenol A : cure characteristics, thermal stability and mechanical property - Ang, Nicholas Rong Jun (2012)
The call for material enhancement with technology has ever been on a constant increment in marine-time applications. In the past decade, most materials used in marine-time application were super-alloys. Steel was used as the primary form of material as it is known for its strength. However, due to the high density of steel, the increasing depth in today’s deep-water oil harnessing has pushed the nature of the material to its limit. With the increase of depth in many folds, the anchors can no longer hold the natural weight of the pipeline results in additional loading within the structures of the pipeline which may lead to a burst in the pipes as seem from the recent oil-spills. Thus, there is a huge and urgent demand for new materials to replace steel that could reduce the weight significantly and provide stronger mechanical strength. The new material of interest is the fiber reinforced composite.